Efeitos dos extratos de Solanum guaraniticum e Syzygium jambos sobre parâmetros bioquímicos e de estresse oxidativo em modelos in vitro e in vivo - Bonfanti, Gabriela (2014)
The use of medicinal plants for the treatment and prevention of disease is a common practice, despite their effects are few studied scientifically. Solanum guaraniticum, also known as false jurubeba, is a medicinal plant widely distributed in Rio Grande do Sul and used for the treatment of gastric and hepatic disorders. Similarly, Syzygium jambos has its leaves, seeds and fruits used for the treatment of diabetes mellitus. Therefore, considering the popularity of the species mentioned above and the lack of data on their pharmacological and toxicological profiles, the aim of this study was to evaluate the effect of leaf extracts of S. jambos and S. guaraniticum on biochemical and oxidative stress parameters in in vitro and in vivo models.The extracts showed vitamin C and phenolic compounds, among which were identified gallic, chlorogenic and ellagic acids, catechin, epicatechin, rutin, quercitrin, isoquercitrin, quercetin and kaempferol in both extracts and caffeic acid only in S. jambos extract. In models of oxidative stress induction, both extracts exhibited anti-hemolytic effect on human erythrocytes and were capable of decrease the process of lipid peroxidation, and this last effect was also observed in kidney, liver and brain tissues of rats, in vitro. In these tissues, both extracts were also able to protect the thiol groups. The extracts showed H2O2 and NO scavenging ability, Fe2+ chelating activity and reducing capacity, proving its antioxidant action. In all assays, the extract of S. jambos was more potent as an antioxidant and also showed tiol-peroxidase - like activity. We observed an inhibition of the activity of δ-aminolevulinic acid dehydratase (δ-ALA-D) in human erythrocytes by both extracts, and the S. guaraniticum was more potent in this assay. It is possible to suggest an involvement of zinc ions of the active site of this enzyme in this inhibition mechanism. The extract of S. guaraniticum administered in vivo, was not able to cause changes in the activity of the enzyme δ-ALA-D, as well as enzymes acetilcholinesterase and N-acetyl-b-D-glucosaminidase. The Artemia salina lethality test showed that both extracts are biologically active. In lymphocytes, in vitro, the extract of S. jambos altered mitochondrial activity and inhibit AChE activity, suggesting an immunomodulatory effect, while the extract of S. guaranticium shows cytotoxic effects. In the acute toxicity evaluation of the extract of S. guaraniticum was possible to identify that the LD50 is greater than 5000 mg/kg and, therefore, this extract can be considered non-toxic for human consumption. Furthermore, although the animals did not show significant bodily, hematological and biochemical changes, the treatment with the extract of S. guaraniticum was able to cause an alteration in the open field test. The reduction in the number of crossing and rearing may indicate a depressant effect, which seems to be delayed and short-lasting. Therefore, the vegetal species studied can be recognized as sources of natural antioxidants and have prospective use in preventive medicine against oxidative stress related diseases, although its popular use should be done with caution until further studies regarding the toxicological profile of the extracts is performed.